The genus Yemmalysus Štusák (Hemiptera: Heteroptera: Berytidae) from China - Cai, Bo; Ye, Zhen; Bu, Wenjun (Zootaxa, 2013)
Species of the genus Yemmalysus Štusák, 1972 from China are treated in this paper: Y. parallelus Štusák, 1972 and Y. brevispinus Cai, Ye & Bu, sp. nov. Scanning electron micrographs of the head, thorax, external scent efferent system and scutellar spine, illustrations of the male genital capsules and parameres of the two species, and a key to the species of this genus are provided to assist in identification. Type specimens of Y. brevispinus sp. nov. are deposited in Institute of Entomology, College of Life Sciences, Nankai University, Tianjin, China.